PENGARUH TAKARAN PUPUK KANDANG AYAM DAN PHONSKA TERHADAP HASIL UBI JALAR VARIETAS CILEMBU - Endang Sufiadi; Odang Hidayat; Suparman Suparman; Roni Assafaat Hadi (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2016)
An experiment was carried out from May to October 2015 at Experimental Field of Agriculture Faculty Winaya Mukti University Tanjungsari Campus, at the altitude of 850 m above sea level, Inceptisols soil order. The objective of these experiment was to study interaction effect of Chicken manure and Phonska Rates on Yield of Sweet Potato Cilembu Variety. Experimental design used was a Randomized Block Design (RBD) in factorial pattern with 2 replications. The fisrt factor named chicken manure rates (A), contain of 4 levels, named : a0 = without chicken manure, a1 = 10 t ha-1, a2 = 20 t ha-1, a3 = 30 t ha-1. Rates of Phonska (P) contain 4 levels, named : p0 = without Phonska, p1 = 400 kg ha-1, p2 = 800 kg ha-1 p3 = 1.200 kg ha-1. Result of experiment showed that interaction between chicken manure and phonska rates was not significant on yield of sweet potato Cilembu variety. Main effect of chicken manure rates and phonska rates were significant on plant dry weigt at one, two, three and four month after planting, weight of first class tuber and total tuber plot-1, while the effect on number of tuber is not significant. The optimum chicken manure rate was 28,87 ton ha-1 with maksimum first class yield 17,96 t ha-1, and optimum chicken manure rate was 27,18 t ha-1 with total tuber yield 20,51 t ha-1. Tuber yield response toward phonska rates was linear.